Nasal cancers, symptoms and upper airway function in woodworkers. Issue 3 (August 1977) - Andersen, H C; Andersen, I; Solgaard, J
Abstract : In 186 cases of nasal cancer diagnosed over the decade 1965-74, in a population of 2-0 million, 114 of 157 ectodermal tumours were found in men. Adenocarcinoma was found in 17 patients, two women and 15 men; 12 of these had a history of occupational exposure to wood dust in the furniture industry. The period of latency was from 28 to 57 years. Among the remaining 99 tumours in men there was occupational exposure to wood dust in 10 cases. Wood dust concentrations in the breathing zone, respiratory symptoms and upper airway function were studied in 68 workers in the furniture industry. The dust concentrations affecting 63% of the workers were higher than 5 mg/m3 (TLV). Middle ear inflammation and common colds were more frequent at high dust concentrations, and the number of workers with nasal mucostasis was directly proportional to the wood dust concentration.